Złoto i srebro jako pieniądz w łacińskiej literaturze patrystycznej okresu późnego cesarstwa rzymskiego - Jundziłł, Juliusz (Vox Patrum, 1987)
The article showed the situations, in which gold and silver are used as a money. The majority of information like these resulted from stylistic convention Fathers of the Church.